Easiness of use and validity testing of VS-SENSE device for detection of abnormal vaginal flora and bacterial vaginosis - Donders, Gilbert G. G.; Marconi, Camila [UNESP]; Bellen, Gert (Hindawi, 2010)
Accessing vaginal pH is fundamental during gynaecological visit for the detection of abnormal vaginal flora (AVF), but use of pH strips may be time-consuming and difficult to interpret. The aim of this study was to evaluate the VS-SENSE test (Common Sense Ltd, Caesarea, Israel) as a tool for the diagnosis of AVF and its correlation with abnormal pH and bacterial vaginosis (BV). The study population consisted of 45 women with vaginal pH ≥ 4.5 and 45 women with normal pH. Vaginal samples were evaluated by VS-SENSE test, microscopy and microbiologic cultures. Comparing with pH strips results, VS-SENSE test specificity was 97.8% and sensitivity of 91%. All severe cases of BV and aerobic vaginitis (AV) were detected by the test. Only one case with normal pH had an unclear result. Concluding, VS-SENSE test is easy to perform, and it correlates with increased pH, AVF, and the severe cases of BV and AV. Copyright © 2010 Gilbert G. G. Donders et al.
Keywords: adult; clinical article; controlled study; disease severity; female; human; microbiology; microscopy; pH; priority journal; sensitivity analysis; vagina discharge; vagina flora; vaginitis; validity